1999
DOI: 10.1016/s0304-3959(98)00197-3
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of nociception I: Responses of 11 inbred mouse strains on 12 measures of nociception

Abstract: It is generally acknowledged that humans display highly variable sensitivity to pain, including variable responses to identical injuries or pathologies. The possible contribution of genetic factors has, however, been largely overlooked. An emerging rodent literature documents the importance of genotype in mediating basal nociceptive sensitivity, in establishing a predisposition to neuropathic pain following neural injury, and in determining sensitivity to pharmacological agents and endogenous antinociception. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
419
2
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 591 publications
(462 citation statements)
references
References 95 publications
40
419
2
1
Order By: Relevance
“…One explanation considers the existence of genetic diversity regarding the exact structure and dimension(s) of chemesthetic receptors. Studies in animals have shown that genetic variability explains differences among individuals in their ability to detect nociceptive stimuli (Elmer et al 1998;Mogil et al 1999). Human psychophysical experiments on detection of nasal chemesthesis from VOCs showed that individual subjects might vary by one or two carbon units in the exact position of the cut-off homolog along a series but, once a subject reaches his or her cut-off, he or she never comes back to detect a larger molecule again .…”
Section: Discussionmentioning
confidence: 99%
“…One explanation considers the existence of genetic diversity regarding the exact structure and dimension(s) of chemesthetic receptors. Studies in animals have shown that genetic variability explains differences among individuals in their ability to detect nociceptive stimuli (Elmer et al 1998;Mogil et al 1999). Human psychophysical experiments on detection of nasal chemesthesis from VOCs showed that individual subjects might vary by one or two carbon units in the exact position of the cut-off homolog along a series but, once a subject reaches his or her cut-off, he or she never comes back to detect a larger molecule again .…”
Section: Discussionmentioning
confidence: 99%
“…However, far less work has been done to study the effects of biology on nanoparticle PK than the effects of material properties on nanoparticle PK. It is perhaps not surprising that we see different results in different mouse strains for clearance, as mouse strain background has a significant impact on biological processes ranging from immune function (42), pain sensation (43), and cancer (44). Outbred WT mice show a large degree of heterogeneity in many measures of immune function, while inbred lab strains of mice show very little intrastrain variation (45).…”
Section: Figurementioning
confidence: 95%
“…Mogil and colleagues attempted to test the effects of muscle insult in their dominantnegative ASIC3 transgenic mice; however, the wild-type controls for ASIC3 transgenic mice do not develop mechanical hyperalgesia to repeated intramuscular acid injections (Mogil et al, 2005), as we previously described (Sluka et al, 2004). Differences are likely related to the strain of the mouse since prior studies demonstrate strain differences in mechanical sensitivity and in different injury-induced animal models of pain (Mogil et al, 1999a;Mogil et al, 1999b). In the current study we utilize congenic mice on a C57BL/6J background, while Mogil and colleagues (2005) utilize mice on an FVB background.…”
Section: Asic3 In Muscle Mediates Mechanical Hyperalgesia Induced By mentioning
confidence: 99%